KAPASITAS PEMERINTAH DALAM PELAKSANAAN PROGRAM REHABILITASI BERSUMBERDAYA MASYARAKAT (RBM) DI KOTA BANDUNG TAHUN 2022-2023 - Mochammad Malik Fajar; Iyep Saefulrahman; Yayan Nuryanto (LPPM Universitas Abdurrab, 2026)
The implementation of the Community-Based Rehabilitation (CBR) Program for persons with disabilities in Bandung City can be considered suboptimal. This is indicated by the low employment and school participation rates among persons with disabilities in the city. In this regard, the capacity of the government in implementing the CBR Program requires examination. This study aims to assess the capacity of the Bandung City Government in implementing the CBR Program, analyzed using Evrim Tan's model, which consists of mobilization, decision-making, implementation, and local capacities. This study employs a descriptive qualitative method. Data were collected through interviews, literature review, and observation. Informants were selected using a purposive sampling technique. The findings reveal that the capacity of the Bandung City Government in implementing the CBR Program is not yet maximal. The mobilization capacity, specifically regarding budget adequacy, has not been sufficient to support program activities. Meanwhile, the planning process has not fully involved persons with disabilities, and communication with the community has not been well-established. Furthermore, a human resources crisis among cadres renders the CBR Program implementation ineffective and inefficient. However, the involvement of local resources is commendable, particularly the engagement of institutions and organizations in assisting the implementation of the CBR Program in Bandung City. Based on these findings, to enhance the government's capacity in implementing the CBR Program, several efforts are necessary: increasing the budget for program activities, improving public socialization to raise awareness for persons with disabilities, and enhancing the skills of cadres through capacity building.